Self-Care Behavior Changes among People with Type 2 Diabetes Mellitus in Kasihan 2 Community Health Center during Covid-19 Pandemic - Indrayana, Sofyan; Mulyanti, Mulyanti; Samutri, Erni; GA Putra, Muhammad; Ngatini, Ngatini; Ummi Nurhidayatul Umami, Ummi; Titanik, Geladis (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2022)
Introduction: People with Type 2 DM (T2DM) tend to experience indirect health risks due to disturbances in aspects of health services and lifestyle during the COVID-19 pandemic. However, information on self-care among people with T2DM during the pandemic is still limited. This study aimed to know the self-care behavior change among T2DM in Kasihan 2 Community health center during the Covid-19 Pandemic.Method: This was a non-experimental study with a cross-sectional approach. An amount as 187 people with T2DM was recruited from a community health center in a rural area by using an accidental sampling technique. We exclude participants who have severe complications and impairment cognitive. Data were self-report administered by using The Summary of Diabetes Self-Care Activities Measure (SDSCA). The Wilcoxon Signed Rank Test was performed to examine the hypothesis.Results: Our study found that the average Diabetic self-care score before the COVID-19 pandemic was 65,257(±11,22), meanwhile self-care score during the pandemic was 59,15(±11,08). Wilcoxon test for SDSCA total score resulted in z coefficient was -9.596 with the p-value equal to 0.00 (<0.05). Several aspects of Diabetic self-care had a significant difference (p<0.05) between before and during the COVID-19 pandemic, such as general diet (z=-9.596); special diet (z=-4,836); physical activity (z=-9.629), and blood glucose monitoring (z=-5.760).Conclusions: There was a significant change in diabetic self-care before and during the COVID-19 pandemic especially in the general diet, special diet, physical activity, and blood glucose monitoring among T2DM in Kasihan 2 Community health center.